HUBUNGAN KEPATUHAN KONTROL DENGAN KADAR GULA DARAH SEWAKTU PADA PASIEN DM TIPE 2 - Ismansyah Ismansyah (MNJ (Mahakam Nursing Journal), 2020)
Management of patients with diabetes mellitus requires cooperation from both patients themselves and families with health workers so that the program can be carried out properly, so that obedient patients exercise control and risk for complications can be prevented. The purpose of this study was to determine the relationship of control adherence with blood sugar levels when in Type 2 DM patients. The design of this study was descriptive correlational with cross sectional approach. The population was 74 Type 2 DM patients. The sample was 70 people with nonprobability sampling with pusposive sampling technique. The research instrument used observation sheets of respondents' visit notes taking DM drugs and observation sheets of blood glucose laboratory results while. Data were analyzed using univariate and bivariate techniques with the Mann Whitney test. The respondents most are obedient in carrying out DM disease control. Blood sugar levels when in the range 105-535 mg / dl with an average GDS of 223.37 mg / dl. There was a relationship of control adherence with the current blood sugar level (p = 0,000).It is expected that DM sufferers improve medication control compliance in order to be able to maintain their health condition by adhering to the re-treatment schedule and asking for family support.